The Price Contagion Effects of Financial Reporting Fraud and Reputational Losses: Evidence from the Individual Audit Partner Level - GUL, Ferdinand A. (Institutional Knowledge at Singapore Management University, 2016)
This study investigates the existence of price contagion effects for the low-quality audits of individual audit partners and the associated reputational losses in China. Low-quality partners are identified as those whose clients have been sanctioned by regulators for financial reporting fraud. Our evidence shows that sanctions induce a significant stock price decline among the contagion firms that share common low-quality partners and common low-quality audit firms; however, the decline is greater for the former. We also find that the price contagion effects of low-quality partners are more pronounced for firms located in regions with weak institutional development and less pronounced for state-owned firms. Finally, we find that low-quality audit partners suffer from reputational losses in terms of a higher likelihood of partner turnover and a reduced market share at the partner level.